Handhelds duke it out for the Internet. - Comerford, R. (IEEE spectrum)
Proponents of personal digital assistants (PDA) say that it will be these hand-held units that tie the on-the-go executive of the future to the Internet. However, looking just as strong is the other big contender for providing wireless Internet access-the next generation cell phone. This article discusses the capabilities and drawbacks of the latest generation of PDAs using the Bluetooth and Wireless Application Protocol networking technologies. The article also discusses the latest cellular phone technology performing similar functions to PDAs. The cost of connecting a PDA to the Internet is also discussed